The Lactate Threshold
In exercise physiology, there have been few topics more frequently investigated, or more vigorously debated than the lactate threshold. It is the details, not the basics that create the big research problems. However, it is the basics that have great application to training and performance. So, we'll stick to those. What is Lactic Acid and Where Does it Come From? When you consume carbohydrate, it consists of several different sugar molecules; sucrose, fructose, glucose to name a few. However, by the time the liver does it's job, all of this sugar is converted to glucose which can be taken up by all cells. Muscle fibers take up glucose and either use it immediately, or store it in the form of long glucose chains called glycogen. During exercise, glycogen is broken down to glucose which then goes through a sequence of enzymatic reactions that do not require oxygen to proceed. All of these reactions occur out in the cell fluid, or cytosol. They can occur very rapidly and yield some ATP in the process. This pathway is called the anaerobic (no oxygen) glycolysis (glucose breakdown) pathway. Every single glucose molecule must go through this sequence of reactions for useful energy to be withdrawn and converted to ATP, the energy molecule, that fuels muscle contraction, and all other cellular energy dependant functions.